Penerapan Model Pembelajaran Struktural Untuk Meningkatkan Hasil Belajar IPA - Raya Emmy Siregar (JURNAL GLOBAL EDUKASI, 2018)
Abstract: The researcher was conducted with the aim to know the improvement of science learning outcomes of students through structural type cooperative learning model. Subjects in this study were students of class VIII.8 with a total of 41 students. the instrument used is a test in the form of multiple problems. The result of the research was obtained in the first cycle test of the total number of students who completed there were 17 students (41.4%), with average score of 64 categories of medium learning ability. In the second cycle, the result of students' learning comprehension test is thoroughly there are 34 students (82,9%) with average score of 74 categories of high learning ability. Thus it can be concluded that cooperative type structural strategies can improve the learning outcomes of science students of class VIII.8 SMP Negeri 1 Kisaran on the material Motion System In Humans. Keywords: structural, motion, human systems. Abstrak: Peneliti ini dilakukan dengan tujuan mengetahui peningkatan hasil pembelajaran IPA siswa melalui model pembelajaran kooperatif tipe struktural. Subjek dalam penelitian ini adalah siswa kelas VIII.8 dengan jumlah 41 orang siswa. intrument yang digunakan adalah tes yang berupa soal berganda. Hasil penelitian diperoleh pada tes siklus I jumlah siswa yang tuntas ada 17 orang siswa (41,4%), dengan rata-rata nilai 64 kategori kemampuan pembelajaran sedang. Pada siklus II hasil tes kemampuan pembelajaran IPA siswa yang tuntas ada 34 orang siswa (82,9%) dengan rata-rata nilai 74 kategori kemampuan pembelajaran tinggi. Dengan demikian dapat disimpulkan bahwa strategi kooperatif tipe struktural dapat meningkatkan hasil belajar IPA siswa kelas VIII.8 SMP Negeri 1 Kisaran pada materi Sistem Gerak Pada Manusia. Kata kunci: struktural, sistem gerak, manusia.